Optimization of Reporting by Using Technology in Order to Create A Reliable Archives Management Effectiveness in Padang City and North Aceh District - Adi Suhendra (Inovbook Publications, 2022)
This research is about Compilation of reports conducted by local governments in Padang City and North Aceh District. This research is considered important because the implementation of the activities of preparing reports is the result of reports on the implementation of activities and the achievement of the performance of government administrators. The population in this study is an area that has made innovations related to administrative innovation by utilizing technology. Meanwhile, the research subject is the innovation created by the City of Padang called the Report Submission innovation through the Regional Development Management Information System (SIMBANGDA) and the innovation in the Tapem Section of North Aceh Regency called Report Compilation Through